The transition from hypertension to hypertensive heart disease and heart failure: the PREFERS Hypertension study - Ekström, Mattias (ESC Heart Fail, 2020)
AIMS: Despite evidence‐based therapeutic approaches, target blood pressure is obtained by less than half of patients with hypertension. Hypertension is associated with a significant risk for heart failure, in particular heart failure with preserved left ventricular (LV) ejection fraction (HFpEF). Although treatment is suggested to be given early after hypertension diagnosis, there is still no evidence‐based medical treatment for HFpEF. We aim to study the underlying mechanisms behind the transition from uncomplicated hypertension to hypertensive heart disease (HHD) and HFpEF. To this end, we will combine cardiac imaging techniques and measurements of circulating fibrosis markers to longitudinally monitor fibrosis development in patients with hypertension. METHODS AND RESULTS: In a prospective cohort study, 250 patients with primary hypertension and 60 healthy controls will be characterized at inclusion and after 1 and 6 years. Doppler echocardiography, cardiac magnetic resonance imaging, and electrocardiogram will be used for measures of cardiac structure and function over time. Blood biomarkers reflecting myocardial fibrosis, inflammation, and endothelial dysfunction will be analysed. As a proxy for HFpEF development, the primary endpoint is to measure echocardiographic changes in LV function and structure (E/e′ and LAVI) and to relate these measures of LV filling to blood pressure, biomarkers, electrocardiogram, and cardiac magnetic resonance. CONCLUSIONS: We aim to study the timeline and transition from uncomplicated hypertension to HHD and HFpEF. In order to identify subjects prone to develop HHD and HFpEF, we want to find biomarkers and cardiac imaging variables to explain disease progression. Ultimately, we aim at finding new pathways to prevent HFpEF.